SCIENTIFIC-PHILOSOPHICAL WAY OF REALITY PERCEPTION AS A MAIN MODE OF MAN – MATERIAL WORLD INTERACTION - Базалук, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
It is disclosed ways of man’s perception of reality and determined the scientific-philosophical way to be the main mode of interaction of planet-cosmic type of an individual with the material world.